Gustav Klimt at home - Bade, Patrick (Frances Lincoln, 2017)
Gustav Klimt at Home explores the influences of Vienna and other places Klimt travelled to and called home on his life and work. Klimt was one of the most prominent members of the Vienna Secession movement. He was both influenced by and shaped the city of Vienna at the turn of the century. His trips to Ravenna, as well as annual summer holidays with the Floge family on the shores of Attersee were also a source of inspiration and influence on his creative output. Fully illustrated, the book features paintings, archive imagery and photographs of the surrounding city and landscape to provide an insight into how the people and places of his life relate to his work
Keywords: Klimt, Gustav -- 1862-1918; Klimt, Gustav / 1862-1918 / Criticism and interpretation; Klimt, Gustav / 1862-1918 / Homes and haunts; Artists / Austria / Vienna / 19th century; Artists / Austria / Vienna / 20th century